2015
DOI: 10.3906/sag-1401-25
|View full text |Cite
|
Sign up to set email alerts
|

Premarital screening of 466 Mediterranean women for serum ferritin,vitamin B12, and folate concentrations

Abstract: Background/aim: Iron, folate, and vitamin B12 serum levels are closely related with dietary habits and have an essential role in the healthy development of a fetus. We aimed to investigate hemoglobin, ferritin, folate, and vitamin B12 levels in preconceptional women in an area where a plant-based diet referred to as Mediterranean cuisine is commonly used. Materials and methods:The study population included 466 women between the ages of 18 and 45 years admitted for thalassemia screening. Sociodemographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In this study, we observed that women who were from low-income families had lower vitamin B12 concentrations and a higher risk of vitamin B12 insufficiency, similar to findings of previous research [13,21,48]. This association could be attributed to the limited availability and affordability of animal-based foods amongst low-and middle-income people [58].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we observed that women who were from low-income families had lower vitamin B12 concentrations and a higher risk of vitamin B12 insufficiency, similar to findings of previous research [13,21,48]. This association could be attributed to the limited availability and affordability of animal-based foods amongst low-and middle-income people [58].…”
Section: Discussionsupporting
confidence: 89%
“…A Jordanian survey of varying age and gender showed that 30.1% of women aged ≥ 19 years were deficient in vitamin B12 (<147 pmol/L) [20], while a Turkish study of non-pregnant women aged 18-45 years noted that the prevalence of vitamin B12 insufficiency among them was lower, at 22% (≤220 pmol/L) [48]. The reason for the difference between our findings and those studies may be because they were conducted in regions with populations that are at a high risk of developing thalassemia and where there is a significant minority (24.9%) of women with anemia [48]. The differences between the two aforementioned studies could be due to the nature of the studies' sample populations.…”
Section: Discussionmentioning
confidence: 99%
“…So, the problems that develop due to consanguineous marriages tend not to be diagnosed early, or are overlooked. Therefore, preconception counselling of adolescent-age women in consanguinity is important (Goossens et al, 2015;Karabulut et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, advanced age (> 60 years) and female gender are frequently associated with increased prevalence. 2,11 Karabulut et al 12 documented a high B12 vitamin deficiency in 21.6% of 466 adult premarital women. In accordance with these data, the prevalence of B12 deficiency was 3.1 times higher in female patients, and male patients were significantly older in our study.…”
Section: Discussionmentioning
confidence: 99%